2018
DOI: 10.5603/mrj.2018.0017
|View full text |Cite
|
Sign up to set email alerts
|

Benign paravertebral cyst of Hattori: A case report and review of literature

Abstract: Hideo Hattori reported the first case of a mediastinal cyst with features characteristic of a Mullerian cyst in 2005. He presented a case of an 18-year-old woman who presented with an abnormal shadow on chest X-ray film during medical examination and who had no other anatomic abnormalities or clinical problems. We present a case of benign cyst within the mediastinum in the left paravertebral space at the level of the aortic arch in a 56-year-old woman. This patient was being investigated for unexplained shortn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…As noted by Idaewor, cysts of Hattori are essentially benign, and surgical removal is only necessary to alleviate patient discomfort. 1 Our reported lesion began as a misdiagnosis, as have several others in the literature. [4][5][6] As Kawaguchi reports, mediastinal Mullerian cysts typically present on CT scans in contact with a vertebral body, a presentation consistent with our study.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…As noted by Idaewor, cysts of Hattori are essentially benign, and surgical removal is only necessary to alleviate patient discomfort. 1 Our reported lesion began as a misdiagnosis, as have several others in the literature. [4][5][6] As Kawaguchi reports, mediastinal Mullerian cysts typically present on CT scans in contact with a vertebral body, a presentation consistent with our study.…”
Section: Discussionsupporting
confidence: 57%
“…Because it is rare for Mullerian cysts to occur outside of the pelvis, and the mediastinum is not included in the secondary Mullerian system, it has been hypothesized that cysts of Hattori are congenital choriostomas. 1,5,10 No embryonic Mullerian structures have been identified in the pleura and pericardium as well. 1 Our patient was unique in the globus sensation and choking sensation that she reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2010, a paper discussing the pathogenesis of cyst of Hattori by Batt et al suggested that the cyst originated from the primary Müllerian tissue similar to the postulated pathogenesis of Mayer-Rokitansky-Kuster-Hauser syndrome (MRKH). This syndrome is characterized by the failure of the Müllerian duct to develop, resulting www.journals.viamedica.pl in absence of the uterus and variable degrees of vaginal hypoplasia or agenesis [8]. Other theories include the notion that Müllerian cysts of Hattori may represent metaplastic changes of the mesothelium into ciliated epithelium [7].…”
Section: Pathogenesismentioning
confidence: 99%